Активизация критического мышления учащихся на уроках географии через саморегулируемое обучение - Шарипова, Д. С. (My University, 2016)
In this article, the author discusses how the formation of self-regulation, self-study activates critical thinking of students. Presents the works of famous psychologists and teachers who have studied the processes of self-regulation. Based on my experience, the author introduces in his practice techniques and methods to develop the skills of self-control of pupils at the school in the study of the subject of geography.
Keywords: self-regulation; self-reliance; self-control; geography; critical thinking; learning activities; student